PKM Pelatihan Pajak Dan Konsultasi Pelaporan Pajak Orang Pribadi - Kaslani; Mulyawan; Irfan Ali; Farra Oktaviani Putri; Haris Burhanudin (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Tax reporting is an obligation that must be fulfilled by every taxpayer, including individuals. However, many individuals still face difficulties in understanding tax regulations and correct reporting procedures, which can lead to errors in reporting or even tax evasion. Through this Student Creativity Program (PKM), training and consultation are provided to enhance the understanding and skills of individual taxpayers in accurately and compliantly reporting taxes according to the applicable regulations. The objective of this program is to provide comprehensive knowledge on taxation for individuals and to offer consultations that can assist them in preparing and accurately reporting their taxes. The methods used in this program include face-to-face training, tax reporting simulation workshops, and individual consultation sessions. The expected outcomes are increased awareness and compliance of individual taxpayers with their tax obligations, as well as their ability to report taxes more accurately and on time. It is anticipated that this program will help reduce errors in tax reporting and increase state revenue through improved tax compliance.